Trench topography in subduction zones: A reflection of the plate decoupling depth - Dasgupta, Ritabrata; Mandal, Nibir (Frontiers in Earth Science, 2022)
Subduction of lithospheric plates produces narrow, linear troughs (trench) in front of the overriding plates at the convergent boundaries. The trenches show a wide variation in their topographic characteristics, such as width, vertical depth, and bounding surface slopes. Benchmarking their controlling factors is thus a crucial step in the analysis of trench morphology. This article identifies the mechanical coupling between the subducting and overriding plates as a leading factor to modulate the topographic evolution of a trench. The maximum depth of decoupling (MDD) is used to express the degree of decoupling at the plate interface. We simulate subduction zones in computational fluid dynamic (CFD) models to show the topographic elements (maximum negative relative relief: D; fore- and hinter-wall slopes: θF and θH; opening width: W) of trenches as a function of MDD within a range 30 to 120 km. Both D and θ strongly depend on MDD, whereas W is found to be relatively less sensitive to MDD, implying that the narrow/broad width of a trench can change little with the plate decoupling factor. We also show that the MDD critically controls the fore-arc stress fields of a trench, switching a compressive to tensile stress transition with increasing MDD. The article finally validates the model findings with well-constrained natural trench topography.